PROSPECT OF DEVELOPMENT OF TILAPIA SEED CULTIVATION BUSINESS WITH BIOFLOC SYSTEM - Gusti Ngurah Sugiana, I; Wayan Arya, I; Nyoman Sadguna, Dewa (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Biofloc technology is a technology that uses bacteria. both heterotrophs and autotropes. These bacteria can convert organic waste intensively into a collection of microorganisms in the form of flocs. The floc formed is utilized by fish as a food source. So it is urgent to research the extent to which biofloc technology is suitable for tilapia hatchery business in the long term. The aim of this study is to be able to provide information to farmers about the feasibility of tilapia aquaculture with a biofloc system. The method used in this research is descriptive method and location determination by purposive sampling with the consideration that the research location has used a biofloc system which previously used conventional cultivation methods. developed in the long term based on a total weighted score of 4,75. The conclusion obtained in this study is that tilapia hatchery efforts feasible are recommended from four aspects. There are several obstacles in aquaculture, including: water quality for tilapia hatchery business with a biofloc system that is polluted due to household waste, obstacles during the rainy season, constraints on feed prices that often increase, disease attacks on tilapia seeds that are stocked, and price games between cultivators.